2020
DOI: 10.1159/000509143
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Sudden Olfactory Loss in the Diagnosis of COVID-19

Abstract: Introduction: Recent reports suggest that sudden smell loss might be a symptom of SARS-CoV-2 infection. The aim of this study was to investigate the frequency of olfactory loss in an outpatient population who presented to a coronavirus testing center during a 2-week period and to evaluate the diagnostic value of the symptom "sudden smell loss" for screening procedures. Methods: In this cross-sectional controlled cohort study, 500 patients who presented with symptoms of a common cold to a corona testing center … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
112
2
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(134 citation statements)
references
References 13 publications
(19 reference statements)
8
112
2
8
Order By: Relevance
“…A total of 11074 COVID-19 patients (mean age 46.7±10.4 years and males 46.9%) were included in the final analysis ( table 1 ). 2 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 The overall prevalence of “loss of smell” in COVID-19 patients was 52.0% (CI: 42.5%-61.6%, I 2 =99.4%) ( Figure 2 ). A total of 21 studies compared these symptoms in COVID-19 patients (n=2196) and controls (n=3425).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 11074 COVID-19 patients (mean age 46.7±10.4 years and males 46.9%) were included in the final analysis ( table 1 ). 2 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 The overall prevalence of “loss of smell” in COVID-19 patients was 52.0% (CI: 42.5%-61.6%, I 2 =99.4%) ( Figure 2 ). A total of 21 studies compared these symptoms in COVID-19 patients (n=2196) and controls (n=3425).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 21 studies compared these symptoms in COVID-19 patients (n=2196) and controls (n=3425). 13 , 14 , 18 , 19 , 21 , 25 , 27 , 28 , 34 , 35 , 36 , 37 , 39 , 40 , 45 , 47 , 48 , 49 , 59 , 60 , 62 “Loss of smell” was associated significantly more in the COVID-19 group compared to non-COVID-19 group (OR: 14.7, CI: 8.9–24.3, p<0.001, I 2 =83.2%) ( Figure 3 ). Among COVID-19 patients, the odds of patients with severe disease and “loss of smell” were significantly low when compared to patients with severe disease and without “loss of smell” (OR: 0.36, CI 0.27–0.48, p <0.01, I 2 =27.4% ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…The included studies consist of a variety of study designs -cross-sectional (n = 22) (12,(16)(17)(18)(19)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41); case-control (n = 3) (42-44); casereport and case series (n = 3) studies (45)(46)(47). Two categories of the MMAT were employed based on the study design to examine the methodological quality of these studies; quantitative non-randomized category for cross-sectional and case-control studies and quantitative descriptive category for case-report and case series ones.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…They were different in design and settings. Majority study design was cross-sectional (about 79%, 22/28) (12,(16)(17)(18)(19)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41);…”
Section: Epidemiological Characteristics Of Included Studiesmentioning
confidence: 99%
“…Olfactory dysfunction and taste dysfunction was noted in 2355 and 2224 patients respectively. In the studies performed by Lauren T Roland et al 4 and Antje Haehner et al 9 Anosmia or ageusia were reported in 95 and 22 patients respectively. Nasal obstruction was reported in 323 patients followed by next common symptom sore throat in 261 patients.…”
Section: Resultsmentioning
confidence: 95%